Shalat Dalam Perspektif Imam Al-Ghazali (Kajian Sufistik) - Maryam, Sitti (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2018)
This paper describes the meaning of prayer according to Imam Al-Ghaali by using the sufisticapproach. This research is descriptive qualitative research. In this context the results of data analysisare presented in descriptive form by means of logical interpretations, so that it can be seen how themeaning of prayer according to Imam Al-Gazali when viewed in terms of sufistik. The method of datacollection that uses in this field is listening method with basic tapping techniques, as well as advancedtechniques of referring to competent non-involvement (SBLC), and recording techniques in theprocess of providing data.The results of this study show: 1) Sufistic approach is a paradigm that focuses on the study of thecleansing of the human soul, which is then used to understand certain problems. 2) Prayers are ritualsperformed by a servant in order to find God where the ritual begins with takbir and ends with greetingsand conditions, besides that there are aspects that must exist when a servant carries out the ritual namelythe presence of the heart, understanding, glorification, fear, hope and shame. 3) There are sixcomponents that must be fulfilled so that the prayer can be accepted by Allah SWT according to ImamAl-Gazali's perspective; Presence of heart, understanding, glorification, fear, hope, and shame.